Does Proximity of Schools Matter? Choice Behavior of High School Leavers Concerning Academic or Professional Training - Carla Sa; Raymond Florax; Piet Rietveld (European Regional Science Association (ERSA), 2003)
Several studies are concerned with the choice behavior of high school leavers. Researchers consider increasingly broader sets of choices within a multinomial choice framework by including transitions to work and to other levels of education. The present paper follows from this literature and identifies the factors behind individual decision-making in the transition from high school to post-secondary education in The Netherlands, in 2000. Given the binary structure of the Dutch higher education system high school leavers follow a hierarchical decision-making process. Initially, they decide whether they want to continue education. Subsequently, the subset that wants to continue education has to make a choice between professional college and the university. We address the determinants of both types of decision in the current paper. Particular attention is given to accessibility aspects, including the geographic location of higher education institutions. The main hypothesis is that individuals who live in closer proximity to a higher education institution are more likely to continue studying after high school, and they are more likely to choose that type of institution. In order to test these hypotheses, we apply mixed discrete choice models to individual-level data on post-secondary education choices. Several institutional characteristics for both professional colleges and universities are considered together with variables controlling for the student's socio-economic background and residential location.
Keywords: 330